Gender Stereotyping and the Jersey Shore: A Content Analysis - Jacqueline S. Anderson; Sharmila Pixy Ferris (KOME: An International Journal of Pure Communication Inquiry)
Reality television is a highly popular genre, with a growing body of scholarly research. Unlike scripted programming, which offers fictional storylines, reality television relies heavily on cast member’s reactions to carefully crafted situations. This study examined the relationship between reality television and gender role stereotyping in a seminal reality television show, MTV’s Jersey Shore. Content analysis was used to conduct an in-depth examination of the first season of Jersey Shore, investigating three gendered issues: physical appearance, social roles and behavioral traits. Findings demonstrated the carefully manufactured relationship between gender role stereotyping and reality television programming in Jersey Shore, and illustrate the development of the female reality show character as related to sexualized behavior and social/emotional gender stereotypes. The depiction of female reality show characters seems to have increased its level of sensationalism, while continuing to be clichéd and conventional, while depiction of male characters is beginning to push the boundaries of being typecast in regards to their physical appearance and role in performing domestic tasks. Additionally, physical alterations on screen were many, warranting further investigation of this behavior.